(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Stone Matrix Asphalt (SMA) is a gap graded mix that has a substantial proportion of coarse aggregates that are kept together by a rich matrix of filler, fibre or polymer stabiliser in a thick asphalt film. This mix is also known as stone matrix asphalt. SMA is regarded as a premium mix by a number of state departments of transportation for use in regions that experience large volumes of traffic and have circumstances that need regular maintenance that may be expensive. The mixture receives a stabilising component such as cellulose fibre in order to prevent the binder from leaching out of the mixture while it is being transported and placed. In the current investigation, an effort is made to evaluate two different bituminous mixes, namely Bituminous Concrete (BC-2) and Stone Matrix Asphalt (SMA-2). Both of these mixes are referred to as bituminous mixes. Within the context of this project, the additive ARBOCEL-ZZ8/1 serves the purpose of stabilising. In this project, a number of different types of tests, including the Marshall Stability test, the Drain down test, the Indirect Tensile Test, and the Rutting Test, are carried out